Self-Concept of Young Offenders Undergoing Non Custodial Sentences in Malaysia - Tharshini, N. K.; Fauziah, Ibrahim; Ezarina, Zakaria (Human Resource Management Academic Research Society, 2020)
Self-concept provides great empirical value in order to understand criminal behaviour among young offenders. Hence, this article is prepared to discuss the level of self-concept of young offenders undergoing non-custodial sentences in Malaysia. A quantitative approach was employed to collect data among 311 young offenders undergoing Community Service Order initiated by the Malaysian Social Welfare Department. Statistical Package for the Social Sciences (SPSS) was used to analyse the data. The result stipulates that majority of the respondents consist of male young offenders aged 20 years old, Malays, single in marital status, and unemployed. The finding also unveiled that young offenders have a moderate level of self-concept (76.2%). As a part of the key recommendation, the Malaysian Social Welfare Department is adjured to revamp the existing Community Service Order module and program in order to improvise the level of self-concept of the young offenders in the near future.